2014
DOI: 10.1007/s40489-014-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Coping in Parents and Caregivers of Children with Autism Spectrum Disorders (ASD): a Review

Abstract: Parents and caregivers of children with ASD have reported significant stress and challenges in caregiving. However, stress coping research in parents and caregivers of children remains limited. This review attempted to close this gap. For this review, 37 studies investigating the (1) underlying themes, (2) contributing factors, and (3) psychological outcomes of ASD-related parental and caregiver coping, were selected from the literature. Results revealed that the two most useful coping resources, i.e., problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 75 publications
(213 reference statements)
6
77
1
2
Order By: Relevance
“…The results of their quantitative study emphasised the relevance of exploring culture-specific coping behaviours. Additionally, the use of qualitative methods to allow for more in-depth exploration of caregiving experiences has been strongly recommended (e.g., Lai et al, 2015;Lai & Oei, 2014).…”
Section: Wellbeing Of Parents Of Children With Asd In the Malaysian Cmentioning
confidence: 99%
“…The results of their quantitative study emphasised the relevance of exploring culture-specific coping behaviours. Additionally, the use of qualitative methods to allow for more in-depth exploration of caregiving experiences has been strongly recommended (e.g., Lai et al, 2015;Lai & Oei, 2014).…”
Section: Wellbeing Of Parents Of Children With Asd In the Malaysian Cmentioning
confidence: 99%
“…Parents of children with ASD use a range of coping strategies and resources when faced with parenting/caregiving stress (Hall and Graff 2011;Hastings et al 2005;Lai and Oei 2014;Luong et al 2009). In a review paper, Lai and Oei (2014) highlighted that parents of children with ASD used both adaptive (e.g., cognitive reframing; seeking social support) and maladaptive (e.g., avoidance and disengagement) coping strategies, with an inclination towards adaptive coping methods such as seeking social support and positive reinterpretation.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics include age (Gray, 2006;Pruitt, Willis, Timmons, & Ekas, 2016), gender (Allik et al, 2006;Lee, 2009;McStay et al, 2014;Mugno et al, 2007), employment status (Dardas & Ahmad, 2014a), and household income (Dardas & Ahmad, 2014a). In fact, a recent review on coping styles among parents of children with ASD reported that age and gender of parents are the most commonly discussed factors (Lai & Oei, 2014). Spousal relationship factors, such as spousal support (Dunn, Burbine, Bowers, & Tantleff-Dunn, 2001), marital satisfaction (Higgins, Bailey, & Pearce, 2005), and marital quality (Harper, Dyches, Harper, Roper, & South, 2013), are other parental characteristics used to investigate the experiences of parents of children with ASD.…”
mentioning
confidence: 99%